Cell phone radiation effect on osteocalcin and bone alkaline phosphatase - Nelwan, Sindy Cornelia; Tedjosasongko, Udijanto; Puteri, Mega Moeharyono; Wicaksono, Dimas Prasetianto; Leo, Leviena Merlynike; Ardiana, Hana Ai; Rahmawati, Siti; Nowwarote, Nunthawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Electromagnetic fields are forces associated with moving electric charges and have electrical, magnetic components and contain electromagnetic energy, one of which is radio frequency (RF) energy which is commonly used in telecommunications. Cell phones are one of the RF electromagnetic radiation devices that can emit 90-2450 MHz waves and are often placed near the head. The human body works like an electromagnetic field in that each cell has its own electrical circuit characteristics. As the number of electromagnetic radiation devices in the environment increases, the electromagnetic balance in the human body may be disturbed by the magnetic waves produced by cell phones. Electromagnetic radiation is known to have the ability to induce oxidative stress, which is characterized by the accumulation of reactive oxygen species (ROS) in tissues. The accumulation of ROS in the body leads to osteoblast cell death. Osteoblasts are needed for mineralization of the extracellular matrix during bone growth. Therefore, bone growth is not optimal and can caused malocclusion. Purpose: This study aims to evaluate the relationship between electromagnetic radiation and osteocalcin and bone alkaline phosphatase (BALP) serum levels. Methods: Experimental laboratory research with a pre- and post-control group design approach was carried out on 12 Rattus norvegicus Wistar strain. Osteocalcin and BALP serum levels were calculated before and after treatment. This study used the t-test as a comparative study (p<0.05). Results: There are significant differences in osteocalcin and BALP values between the treatment groups before and after treatment. Conclusion: Cell phone radiations (electromagnetic field exposure) reduce osteocalcin and BALP serum levels.